Validity and participation: implications for school comparison of Australia's National Assessment Program. Issue 6 (2nd November 2018) - Thompson, Greg; Adie, Lenore; Klenowski, Val
Abstract: The National Assessment Program – Literacy and Numeracy (NAPLAN) in Australia is a series of literacy and numeracy tests that are used for purposes of school comparison. This paper argues that a key question for this use lies in whether or not this is a reasonable, or valid, use of the test data. Using Kane's argumentative approach to validity, this paper argues that the comparisons of the quality of student achievement made available on the My School Website have low validity due to the lack of regard to rates of participation in schools. In bringing together the literature that addresses the 'new governance' of education through testing and an approach to validity that addresses the technical aspects of test score interpretation, with the ethics of how test scores are used and applied, this study identifies validity as an important consideration in comparative analyses of student achievement data. The identification of the need to consider participation in such comparisons through the application of the argumentative approach to validity highlights the contribution of this article not only to the testing field but also to critical policy literature.